SPACE EFFICIENCY BY IMPLEMENTING MULTIFUNCTIONAL FURNITURE IN TYPE 33 HOUSING - Farida, Ariesa; Amalia, Kiki Putri; Liritantri, Widyanesti; Budiono, Irwana Zulfia; Laksitarini, Niken (Universitas Telkom, 2024)
Housing is a basic human need, the more dense urban areas result in the ef ectiveness of landas aresidential area must be carried out. Currently, the development of type 33 housing has resulted in the need for multifunctional furniture to save space for activities, which is a growing trend. Based on the results of discussions with the developer on residential type 33, it is planned that there is a need for appropriate planning and research on the use of multifunctional furniture as a space saving solution. The object of studyto be studied is in Bogor City, West Java Province with a residential area of 33m2 and a land area of 60m2consisting of a living room, dining room and pantry, two bedrooms and one bathroom. Based on the problemsabove, the purpose of this study is to examine the design of multifunctional furniture that can accommodatethe activities and behavior of occupants, where multifunctional furniture is one of the solutions to maximizelimited space in dwellings. The purpose of this research is to produce the right solution for the choiceof multifunctional furniture that is felt to be most needed to accommodate user activity and maximize space. The research method used is a qualitative method by examining primary data from survey results and questionnaires as well as secondary data from literature studies to be able to produce the right multifunctional furniture designs for type 33 housing. Keyword : Interior Design, Multifunctional Furniture, Type 33 Housing